A fluorescence sensor for thiram detection based on DNA-templated silver nanoclusters without metal ion-mediator. (1st July 2023) - Yang, Ziyan; Hu, Lingling; Ning, Keke; Wu, Yuan; Liang, Jiangong
Graphical abstract: In this detection system, single stranded DNA sequences were used as templates for the formation of fluorescent DNA-AgNCs with a maximum emission at 674 nm under 610 nm excitation wavelength. After adding thiram, the fluorescence intensity of DNA-AgNCs could be effectively quenched due to strong competition interaction between thiram and silver atoms of DNA-AgNCs without additional metal ion-mediator. Therefore, a rapid "mix and detect" approach for thiram detection was developed. Highlights: Thiram interacts strongly and competitively with silver atoms of DNA-AgNCs. A "mix-and-detect" thiram sensor based on DNA-AgNCs is developed. Sensing relies on thiram-triggered quenching effect on DNA-AgNCs fluorescence. This sensor enables rapid detection of thiram residues in real samples within 10 min. Abstract: In this work, we firstly found a strong competitive interaction between thiram and silver atoms of DNA-templated silver nanoclusters (DNA-AgNCs), leading to fluorescence quenching of DNA-AgNCs without additional metal ion-mediator. Furthermore, this thiram-induced fluorescence quenching phenomenon was used to develop a sensor for thiram detection. This fluorescence sensor exhibited good linearity with thiram concentration from 0.20 to 2.0 μM and 0.012–0.20 μM under optimized conditions, with a low detection limit of 0.2 μM and 0.01 μM, respectively. Moreover, this sensor showed superior selectivity towards thiram, and its practicability was verified in apples and soil. This study provides a convenient and rapid "mix and detect" approach for thiram detection within 10 min, suggesting its potential for rapid on-site evaluation of thiram in real samples.